Prevalence Of Current Tobacco Use Among Secondary Students In Nepal: A Meta-Analysis - Dhungana, Raja Ram; Khanal, MK; Baniya, A (Journal of Chitwan Medical College, 2014)
Tobacco use continues to rise among young people in middle and low income countries, causing high premature death and disability. Most importantly, its initiation starts mainly during adolescence and persists for whole life. We conducted this meta-analysis to estimate the prevalence of current tobacco use among lower secondary to higher secondary students in Nepal. We searched and identified the studies which were published between 2003 and 2013 using MEDLINE, Google Scholar and NEPJOL. From five selected studies, total 7,832 eligible students were included in analysis. Considering the high degree of variability (Q = 82.6, I2 = 95%) among selected studies, we used random effects model to estimate the weighted prevalence of current tobacco use and found as 13.9 % (10.2-17.5). This result shows that current tobacco use among lower secondary to higher secondary students still remains high, which compels an effective implementation of tobacco control programs and policies. Journal of Chitwan Medical College 2013; 3(4); 1-5 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9544